Evaluation of the Morning Worship Practice Program at Madrasah Ibtidaiyah Using the CIPP Model in Building Students’ Religious Character - Okta Riansyah Al Rahman; Siti Zakia Fuadatinnur; Nur Kamila Hadia Rahmah; Zawaqi Afdal Jamil (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2026)
Based on the results of the study using the CIPP evaluation model (Context, Input, Process, Product), the morning worship practice program at Madrasah Ibtidaiyah has been running quite well. In the context aspect, the program is aligned with the madrasah’s vision of forming students’ religious character. In the input aspect, infrastructure, teacher support, and student involvement are adequate, although some supporting facilities still require improvement. In the process aspect, the implementation of morning worship activities runs routinely and in a directed manner, though the discipline of some students still needs further guidance. Meanwhile, in the product aspect, the program has a positive impact on worship habituation, disciplined attitudes, and the improvement of students’ morals in daily life. Therefore, the morning worship practice program is worthy of being maintained and developed so that the results obtained become more optimal.